Стихи о зиме - Маршак Самуил Яковлевич (Малыш, читай!, 2021)
Экземпляры: ф.13 (20220314) / Инвентарный номер: 62003 / Цена: / Сис.шифр: 84(2=411.2)6-5 / Авт.знак: М 30 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)6-5